‘Cost’ calculations as a barrier to gaining information under the Freedom of Information Act 2000 from the police in England and Wales - Kingston, Sarah (Policing and society, 2019)
Previous research has identified the methodological value of using the Freedom of Information Act 2000 (FOIA) to gain access to information held by the police, as well as its limitations. Very little attention, however, has been paid to the ways in which the police calculate the cost of FOI compliance and utilise cost exemptions to deny access to information. In this article, we present our empirical findings from our FOI requests made to the police in England and Wales that demonstrates how cost calculations became a barrier to our request for information. In addition, the responses received show that there were significant differences between the calculated cost needed to retrieve the information, the reasons given for the refusal for access to information, as well as regional variations with FOI compliance. We argue that excessive cost calculations, given as a reason for not providing access to information by the police, is a ‘metric’ for institutional limitations in data recording and data management. Furthermore, in a time of ‘austerity’ we suggest that with increases in police funding cuts the calculated cost of FOI compliance will increase, thereby undermining police transparency and accountability. We therefore question claims that the FOIA is a ‘powerful’ tool that social researchers should use more often.